Selective Emission Fabric for Indoor and Outdoor Passive Radiative Cooling in Personal Thermal Management - Yu, Haijiao; Lu, Jiqing; Yan, Jie; Bai, Tian; Niu, Zhaoxuan; Ye, Bin; Cheng, Wanli; Wang, Dong; Huan, Siqi; Han, Guangping (Nano-Micro Letters, 2025)
Radiative cooling fabric creates a thermally comfortable environment without energy input, providing a sustainable approach to personal thermal management. However, most currently reported fabrics mainly focus on outdoor cooling, ignoring to achieve simultaneous cooling both indoors and outdoors, thereby weakening the overall cooling performance. Herein, a full-scale structure fabric with selective emission properties is constructed for simultaneous indoor and outdoor cooling. The fabric achieves 94% reflectance performance in the sunlight band (0.3–2.5 µm) and 6% in the mid-infrared band (2.5–25 µm), effectively minimizing heat absorption and radiation release obstruction. It also demonstrates 81% radiative emission performance in the atmospheric window band (8–13 µm) and 25% radiative transmission performance in the mid-infrared band (2.5–25 μm), providing 60 and 26 W m−2 net cooling power outdoors and indoors. In practical applications, the fabric achieves excellent indoor and outdoor human cooling, with temperatures 1.4–5.5 °C lower than typical polydimethylsiloxane film. This work proposes a novel design for the advanced radiative cooling fabric, offering significant potential to realize sustainable personal thermal management. Highlights: 1 Full-scale structure fabric across 0.3-25 μm was fabricated for enhanced sunlight reflectance (94%) and reduced mid-infrared reflectance (6%). 2 Transmission (25%) and emission (81%) characteristics for thermal radiation release. 3 Indoor and outdoor cooling fabric in personal thermal management.